Enhanced interaction of molecular oxygen with amino acid complexes of silver and gold clusters - Manzoor, Dar; Pal, Sourav (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
Density functional theory calculations have been carried out to study the effect of amino acid adsorption on the reactivity of silver and gold clusters with molecular oxygen. It is found that the amino acids glycine and alanine form stable complexes with both Ag-4 and Au-4 clusters. However, the extent of interaction is more in the case of the Au-4 cluster, as reflected from the increase in binding energy in the amino acid Au-4 complexes. Our results confirm that the adsorption of amino acids glycine and alanine enhances the reactivity of Ag-4 and Au-4 clusters towards O-2 molecule. The enhanced reactivity of O-2 molecule towards the amino acid metal cluster complexes is manifested by an increase in the O-2 binding energy and a decrease in the M-O (M = Ag, Au) bond length. Moreover, it is found that the co-adsorption of amino acids and O-2 molecule on the Ag-4 and Au-4 clusters is cooperative.
Keywords: Amino acid complexes; Density functional calculations; Gold clusters; Metal clusters; Silver clusters; Theoretical chemistry

From ``Cosmic Cooking'' to chemistry of the future: a collective dialogue on chemistry as a tribute to Prof. Sourav Pal. - Roy, Soumyajit; Krishnamurty, Sailaja; Schoefberger, Wolfgang (Frontiers in Chemistry, 2022)
Keywords: cosmic cooking; coupled cluster and density functional calculations; dialogue on chemistry; pincers porphyrinoids and oxometalates; small molecule activation; Theoretical chemistry